1992
DOI: 10.1128/jb.174.9.2851-2857.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, nucleotide sequence, and expression of the Escherichia coli fabD gene, encoding malonyl coenzyme A-acyl carrier protein transacylase

Abstract: We report the cloning and nucleotide sequence of the gene encoding malonyl cocnzymc A-acyl carrier protein transacylasc of Esciwrichiu co/i. Malonyl transacylasc has been overexpressed 1.55.fold compared to a wild-type strain, Overexpression of this enzyme alters the fatty acid composition of a wild-type E. coli strain; increased amounts of ris-vacccnate arc incorporated into the mcmbranc phospholipids. Mulonyl transacylase; Malonyl-CoA: Acyl transferase; Fatty acid biosynthesis 1. 1NTRODUCTION Malonyl coenzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 35 publications
0
71
0
Order By: Relevance
“…Hence, the evolutionary origin for MdcH may be a gene operating in the synthesis of polyacetate compounds. Recently, the fabD gene of E. coli has been cloned [26,27] and the structure of its gene product determined [28]. The active site of the enzyme is related to a/b hydrolases where SerHis and Asp/Glu operate together as a charge relay system.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the evolutionary origin for MdcH may be a gene operating in the synthesis of polyacetate compounds. Recently, the fabD gene of E. coli has been cloned [26,27] and the structure of its gene product determined [28]. The active site of the enzyme is related to a/b hydrolases where SerHis and Asp/Glu operate together as a charge relay system.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid cultures of recombinant E. coli were grown in LB broth at 37°C with either 150 g/ml ampicillin or 25 g/ml kanamycin, according to the selection marker present on the plasmid. Strain LA2-89, a thermosensitive E. coli fabD mutant (fabD89), was a generous gift from A. R. Stuitje (16). E. coli C41(DE3), which expresses the T7 RNA polymerase, was used as a host for the overproduction of M. tuberculosis AcpM and mtFabD and was kindly provided by B. Miroux and J. E. Walker (19).…”
Section: Methodsmentioning
confidence: 99%
“…fatty acid or polyketide synthases has demonstrated that a serine, such as Ser-92 in the E. coli FabD protein (16,22,25), is the active nucleophilic residue of these enzymes. During its transfer from malonyl-CoA to ACP, the malonyl moiety is transiently attached to this serine to form a stable malonyl-serine enzyme intermediate (26).…”
Section: Construction and Activity Of Various Mtfabd Mutant Proteins-mentioning
confidence: 99%
See 1 more Smart Citation
“…The following primers were used: (1) 5' -GAATTGCCGCTCGTCTAGAATCTG-3 ' which introduces a Xba I site 130 bp upstream of the starting ATG of the coding region [ 31 ]; (2) 5' -GCGGATCCGAGAACCCTGTCCAG-GG-3', which introduces a Bam HI site at the 3' end, beyond the stop codon, 40 bp into the coding region of the E. coIifabD gene [32]. The following thermal cycle was used: denaturation at 94 ° C for 30 s; annealing at 52 ° C for 60 s; and extension at 72 °C for 90 s, repeated 30 times.…”
Section: Cloning Of the E Coli Fabh Genementioning
confidence: 99%